Stress/strain state for critical components of a jet engine aeronautical compressor. (October 2020) - Cesari, G.; Panella, F.W.; Pirinu, A.
Abstract: In order to prevent in-flight fatigue failure, a numerical analysis of in service-operative cases is an useful approach for preliminary evaluation of most stressed and critical zones in components of aeronautical engine. The zero-stage compressor rotor disk and blades represent one of the most critical part of aircraft turbojet. This paper presents a verification FEM analysis of this component. An accurate 3D scanning was performed to reconstruct both blade and disk real geometry and the detailed point cloud was obtained and opportunely elaborated by using specific software to generate CAD sections and volumes given in input to finite element analysis. The stress field due to different operating conditions is studied for a suitable evaluation of the most stressed and critical areas where a failure may occur, particularly near the rotor connection under contact conditions. FEM and flight data analysis are finally used for a subsequent fatigue life verification, based on classical Palmgren Miner' rule. The suggested procedure for verification of engine aeronautical component is here optimized for maintenance program improvements.